Performance of elevated energy pile groups with different pile spacing in clay subjected to cyclic non-symmetrical thermal loading. (July 2021) - Ng, C.W.W.; Farivar, A.; Gomaa, S.M.M.H.; Shakeel, M.; Jafarzadeh, F.
Abstract: There is an increasing interest and use of energy foundation worldwide. Full-scale tests, physical model tests at one Earth's gravity and at elevated gravity in a geotechnical centrifuge and numerical simulations have been widely reported in the literature. Almost all studies have focused on single energy piles (EPs) and pile groups subjected to symmetrical thermal loads, although it is not unusual to have energy pile groups stressed by non-symmetrical thermal loads. In this study, a series of non-symmetrical thermal loading centrifuge model tests were conducted in saturated soft clay (OCR = 1.7), which is much vulnerable to temperature changes. The tests aim to investigate the effects of pile spacing on the serviceability of floating energy pile groups. Fifteen cycles of non-symmetrical thermal loading are applied to three EPs in 2 x 2 elevated energy pile groups with 3D and 5D (D denotes pile diameter) pile spacing. The thermally induced irreversible settlement and tilting in the 3D-pile group are 200% and 300% larger than those in the 5D one, respectively. Contrary to the 5D-pile group where the serviceability criteria (EN 1997-1:2004) are satisfied, the settlement and tilting are 30% and 200% larger than the criteria in the 3D one, respectively. Highlights: Centrifuge modelling of pile spacing effects on thermo-mechanical interactions between piles within energy pile groups. Influence of thermal interaction on the displacement and tilting of floating elevated energy pile groups. Evaluation of increasing pile spacing on satisfying serviceability limit state at floating energy pile groups in soft clay.